Association between induced abortion and suicidal ideation among unmarried female migrant workers in three metropolitan cities in China: a cross-sectional study - Mengyun Luo; Xueqin Jiang; Ying Wang; Zezhou Wang; Qiuming Shen; Rui Li; Yong Cai (BMC, 2018)
Abstract Background Despite reports of mental health issues, suicidality has not been closely examined among the migrant population. The association between induced abortion and suicidal ideation is unknown among unmarried female migrant workers of reproductive age in China. This study aims to examine induced abortion and suicidality among the Chinese migrant population. Methods We recruited 5115 unmarried female migrant workers during 2015 to 2016 from Shanghai, Beijing and Guangzhou, and collected demographic, psychosocial, reproductive and mental health information using structured questionnaires. We used logistic regression models to examine the association between lifetime induced abortion and suicidal ideation during the past year among the subjects. Results Overall, 8.2% of the subjects had suicidal ideation during the past year, and 15.5% of the subjects experienced induced abortion. Induced abortion was associated with nearly twice the odds of having past-year suicidal ideation (Odds ratio, OR = 1.89; 95% confidence interval, CI: 1.46, 2.44) after adjusting for age, education, years in the working place, tobacco use, alcohol consumption, daily internet use, attitude towards premarital pregnancy, multiple induced abortion, self-esteem, loneliness, depression, and anxiety disorders. The association was stronger in those aged > 25 (OR = 3.37, 95% CI = 2.16, 5.28), with > 5 years of stay in the working place (OR = 2.98, 95% CI = 2.02, 4.39), the non-anxiety group (OR = 2.28, 95% CI = 1.74, 3.00), and the non-depression group (OR = 2.94, 95% CI = 2.08, 4.15). Conclusions Induced abortion was associated with increased odds for suicidal ideation among the unmarried female migrant workers in urban cities in China. More attention should be paid to the mental health of the population.